2021
DOI: 10.3844/ajeassp.2021.129.138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Soil Particle Characterization on Internal Friction Angle

Abstract: One of the critical design parameters used in evaluating soil structure is the friction angle, derived from Mohr's Circle failure criterion. The soil friction angle is an engineering parameter estimated in the laboratory to quantify the soil shear strength in geotechnical applications. This paper indicates an experimental study investigating the impact of particle size on different sandy soils shear strength behavior. The direct shear test equipment is useful for simulating various stress regimes to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
5
8
0
1
Order By: Relevance
“…These results seem to be consistent with other research (e.g. Rasti et al (2021)) which found that soils with bigger D 50 and uniformity coefficients have higher friction angles. However, soil 3 gives a lower friction angle than soil 2; a possible explanation for this might be that the average data used in this study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results seem to be consistent with other research (e.g. Rasti et al (2021)) which found that soils with bigger D 50 and uniformity coefficients have higher friction angles. However, soil 3 gives a lower friction angle than soil 2; a possible explanation for this might be that the average data used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…It confirms clearly that shear strengths of samples with bigger D 50 are higher than mixtures with smaller ones; therefore, particle size distributions of sands play a significant role in the shear strength of samples [31]. It is encouraging to compare this figure with that found by Rasti et al (2021) [28], who also found that with increasing D 50 , the peak shear strength of samples increases. One unanticipated finding in Figure 5(b) is that sand 4 has friction angle of about 50°, however this magnitude is also reported in Bareither et al (2008) [32], Sladen et al (1986) [31].…”
Section: Shear Strengthsupporting
confidence: 70%
See 3 more Smart Citations